355 Growth performance, organ weights, thyroid hormone levels, and hindgut pH of nursery pigs fed diets containing cold-pressed canola cake without or with resistant starch - Lee, Jung Wook (J Anim Sci, 2019)
An experiment was conducted to determine effects of reducing cecal and colonic pH through dietary inclusion of high-amylose cornstarch (HA-starch) on growth performance, organ weights, and blood parameters of nursery pigs fed cold-pressed canola cake (CPCC). A total of 240 pigs (initial BW = 7.1 kg) were housed in 40 pens (6 pigs/pen) and fed 4 diets (10 pens/diet) in a randomized complete block design for 28 d. Four diets were a basal diet with CPCC at 0 or 40%, and with HA-starch at 0 or 40% in a 2 × 2 factorial arrangement. Diets were fed in 2 phases of 14 d each. At the termination of the experiment, one pig per pen was euthanized for determining organ weights, blood parameters, and hindgut pH of pigs. Dietary CPCC reduced (P < 0.05) overall average daily gain (ADG) by 15%; increased (P < 0.05) liver and thyroid gland weights relative to BW by 27 and 64%, respectively; and reduced (P < 0.05) serum tetraiodothyronine (T4) level from 30.3 to 17.8 ng/mL. Dietary HA-starch reduced (P < 0.05) overall ADG, thyroid gland weight relative to BW, cecal and colonic pH; but increased (P < 0.05) colon weight and tended to increase (P = 0.062) serum T4 level. Dietary CPCC and HA-starch interacted (P = 0.024) on the thyroid gland weight relative to BW such that dietary CPCC increased (P < 0.05) thyroid gland weight of pigs fed HA-starch-free diet (120 vs. 197 mg/kg of BW), but not of pigs fed HA-starch-containing diet (104 vs. 130 mg/kg of BW). In conclusion, dietary CPCC reduced growth performance, increased metabolic activities of liver and interfered with thyroid gland functions of nursery pigs. However, the negative effects of dietary CPCC on thyroid gland functions of pigs were alleviated by dietary HA-starch.